The Ethics and Intentions of Writing Family - Neale, Lesley (Oklahoma Sate University, USA, 2017)
This paper discusses the ethical challenges of writing family memoir/biography; a task I undertook to know more about my grandmother's life and to discover the identity of my grandfather. Life writing of this sort necessitates balancing diverse responsibilities: those to the subject, to family members, and to the integrity of the narrative. The ethics of such writing are complicated; a workable solution is implementing relational ethics, as used by ethnographers. These principles are relevant to contemporary women's life writing, which often encompass disparate narrative conventions. I begin by exploring academic and author P J Eakin's understanding of writers' responsibilities. The paper uses examples from Australian writer Drusilla Modjeska's Poppy and British author Doris Lessing's Alfred and Emily, as well as my own work. Within the context of Eakin's principles I address an author's intentions regarding the mother/daughter bond in the works of daughter/writers, and the oral storytelling roots of life writing. The paper particularly considers the inclusion of fictional material within memoir/biography and how this slants ethical issues. The latter part of the paper focuses on the concept of relational ethics as advocated by both author Carolyn Ellis, the developer of autoethnography, and Australian feminist academic Marilyn Metta. Within that framework I consider the effect of revealing family secrets, and writing of subjects no longer alive. I conclude by suggesting that a writer may be guided by self-questioning and by disclosures of intent within the narrative. My perspective is that of a white, Western woman, an ethnicity shared by the female subjects of my life writing.